2015
DOI: 10.1007/s10840-015-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the clinical implications of adenosine triphosphate in terms of the prediction of reconnection sites in cases with electrical isolation of the pulmonary veins

Abstract: DC sites implying RC sites had a weak agreement, and other options to predict RC sites will be required to improve the clinical benefit of CA of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In order to have reliable information about adenosine's ability to predict outcome, it appears to be extremely important to understand if a vein reconnects in the same spot with DC. Okishige and coworkers [ 35 ] performed a prospective study to assess the predictive value of the response to adenosine in terms of identifying the reconnection sites associated with AF recurrence. In their study, sites of DC were tagged using a three-dimensional mapping system and left unablated.…”
Section: Prediction Of Reconnectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to have reliable information about adenosine's ability to predict outcome, it appears to be extremely important to understand if a vein reconnects in the same spot with DC. Okishige and coworkers [ 35 ] performed a prospective study to assess the predictive value of the response to adenosine in terms of identifying the reconnection sites associated with AF recurrence. In their study, sites of DC were tagged using a three-dimensional mapping system and left unablated.…”
Section: Prediction Of Reconnectionmentioning
confidence: 99%
“… (a) Adenosine testing results and PV reconnection rate at redo procedure in Lin et al [ 34 ]. (b) Example of redo procedure reconnection sites that totally differed from DC sites at first procedure [ 35 ]. DC: dormant conduction.…”
Section: Figurementioning
confidence: 99%
“…We previously reported that the agreement between the DC and reconnection sites during the re-do session yielded a weak relationship after an irrigated RF ablation [14]. However, all the reconnection sites that were documented in the re-do session were identical to the DC sites in the first session, which was contrary to the cases with irrigated RF ablation [14]. In addition, the spontaneous reconnection sites occurring during the waiting period also differed from the DC sites during the first session of the PVI using the CB.…”
Section: Clinical Implication Of the Ablation For The DC Sitesmentioning
confidence: 98%
“…They documented late PV reconnection 2 months after the initial PVI in 51 (11%) PV segments, and there was no difference in the proportions of segments that did and did not exhibit dormant conduction but did exhibit late PV reconnection at the time of repeat study (14% vs. 10%, respectively; P = 0.524). Okishige [ 1 8 _ T D $ D I F F ] et al [24] reported that late reconnection sites differed from dormant conduction sites in 20 patients (69%) of 91 patients, that late reconnection sites were identical to dormant conduction sites in 11.5%, and that late reconnection sites involved both dormant conduction and other sites in 19.5%. Lin [ 1 9 _ T D $ D I F F ] et al [22] and Das [ 1 7 _ T D $ D I F F ] et al [23] eliminated dormant PV reconnection by means of additional ablation, and Okishige [ 1 8 _ T D $ D I F F ] et al [24] left dormant PV conduction un-ablated, but the results were similar.…”
Section: Comparison Of Dormant La-pv Conduction and Late Pv Reconnection Sitesmentioning
confidence: 99%
“…Okishige [ 1 8 _ T D $ D I F F ] et al [24] reported that late reconnection sites differed from dormant conduction sites in 20 patients (69%) of 91 patients, that late reconnection sites were identical to dormant conduction sites in 11.5%, and that late reconnection sites involved both dormant conduction and other sites in 19.5%. Lin [ 1 9 _ T D $ D I F F ] et al [22] and Das [ 1 7 _ T D $ D I F F ] et al [23] eliminated dormant PV reconnection by means of additional ablation, and Okishige [ 1 8 _ T D $ D I F F ] et al [24] left dormant PV conduction un-ablated, but the results were similar. We documented absence of dormant PV conduction at the time of the index ablation procedure in a high proportion (82%) of sites showing late PV reconnection at the time of repeat ablation for AF recurrence.…”
Section: Comparison Of Dormant La-pv Conduction and Late Pv Reconnection Sitesmentioning
confidence: 99%